Exploring acupuncture as a therapeutic approach for tic disorders: a review of current understanding and potential benefits - Haoyang Liu; Chunping Wang; Hongbin Zhang; Mohammad J. Rezaei (Frontiers in Neurology)
Tic disorders (TD) refer to a condition where individuals experience recurring motor movements (e.g., eye blinking) and/or vocalizations (e.g., throat clearing). These disorders vary in terms of duration, cause, and manifestation of symptoms. Tourette’s syndrome (TS) involves the presence of ongoing motor and vocal tics for a minimum of 1 year, with fluctuating intensity. Persistent chronic motor or vocal tic disorder is characterized by either motor or vocal tics (not both) present for at least 1 year. Provisional TD presents with either motor or vocal tics (not both) that have been present for less than 12 months. Though medications like Aripiprazole and dopamine receptor blockers are frequently prescribed, their potential unwanted consequences increase, may result in low adherence. In an effort to improve and broaden the care available for children diagnosed with TD, alternative methods such as acupuncture are being investigated and considered. Acupuncture is a method of traditional Chinese medicine that includes the placement of thin needles into particular areas of the body in order to correct any disruptions or irregularities. Research has demonstrated that acupuncture can help regulate abnormal brain function and relieve tic symptoms in individuals with TD. Additional studies are required to fully evaluate the usefulness of complementary treatments in addressing TD in young individuals, despite its common usage. Herein, we summarized the therapeutic effects of acupuncture in the treatment of TD.